Effectiveness of the Game-Based Literacy Learning Model as an Innovation in Beginning Reading Learning for Second Grade Elementary School Students - Irma Irma; Yusmah Yusmah; Aswadi Aswadi; Jamaluddin Ahmad; Nuraini Kasman; Syamsu T (Institut Teknologi Pendidikan Indonesia, 2026)
Low early reading skills in lower-grade elementary school students are often caused by the use of less varied and teacher-centered learning strategies. This study aims to deeply examine the effect of the Game-Based Literacy Learning model on improving early reading skills in second-grade students at State Elementary School 2 Rijang Panua. The research method used was a quasi-experiment with a non-equivalent control group design. Data collection was carried out through reading ability tests covering aspects of letter recognition, syllables, and simple sentences, reinforced by observations of learning activities. Data analysis techniques used descriptive and inferential statistics to compare the achievements between the experimental group and the control group. The results showed that the application of the learning model had a significant impact on increasing students' literacy skills. The group that received the game-based learning model intervention experienced a much higher increase in average scores compared to the group with conventional methods. Statistical analysis proves that this model provides a dominant contribution to students' reading success. The conclusion of this study is that the Game-Based Literacy Learning model is an effective learning innovation and is feasible to be implemented to accelerate early reading skills. This strategy is able to create an interactive and enjoyable learning environment, thereby optimizing students' cognitive engagement.